De Gruchy and his holistic model of theology and development in South Africa and beyond - Gift Masengwe (Verbum et Ecclesia)
This study reflects on Steve de Gruchy’s holistic model of theology and development (TD), emphasising his commitment to justice, human dignity and social transformation in the context of post-apartheid South Africa. De Gruchy was a notable South African theologian whose scholarship significantly influenced development theory, public theology and social ethics. This article is presented in response to the commemoration of 50 years of scholarship at the Research Institute of Theology and Religion at the University of South Africa, and the question is: How does De Gruchy’s holistic model of TD inform our understanding of socio-ecological, political and economic challenges in South Africa, and what implications does it have for development practices both locally and globally? This study employs an interdisciplinary approach, integrating theological analysis with development theory, drawing from De Gruchy’s works and contextual examples. It examines the historical injustices in South Africa, critiques neoliberal economic paradigms and emphasises participatory frameworks for social change. Findings reveal that De Gruchy advocates for TD that transcends economic metrics, highlighting ecological, social and spiritual dimensions. His emphasis on integrated approaches, such as the Sustainable Livelihoods Framework, illustrates the necessity of empowering marginalised communities. The role of faith communities as catalysts for social change underscores the potential for constructive engagement between secular and religious sectors. This study is significant as it reiterates the relevance of De Gruchy’s insights in addressing ongoing development challenges, advocating for a reconceptualisation of TD that intertwines theory and praxis, promoting collaborative solutions in the African context and beyond.